Unclean cooking fuel use and stillbirth in Ghana: evidence from the 2022 DHS - West, Kirstin P.; Sznajder, Kristin K.; Hwang, Grace; Sauve, Hannah E.; Roba, Kedir Teji; Baatiema, Leonard; Kenu, Ernest; Noora, Charles L.; Gizaw, Abraham Tamirat; Yilma, Abebayehu N. (Frontiers in Global Women's Health, 2025)
IntroductionStillbirth remains a major public health issue in low- and middle-income countries (LMICs). Ghana's 2021 stillbirth rate (21.4 per 1,000 births) exceeds the United Nations Sustainable Development Goal (SDG) target of 12 per 1,000 births by 2030. Unclean household cooking fuels have been associated with adverse pregnancy outcomes, including stillbirth. In Ghana, women conduct about 64% of household cooking, often in poorly ventilated settings with particulate levels above World Health Organization (WHO) guidelines. We assessed the association between household cooking fuel type and stillbirth among Ghanaian women.MethodsWe conducted a cross-sectional analysis using data from the 2022 Ghana Demographic and Health Survey. The sample included 10,654 women aged 15–49 years with ≥1 recorded pregnancy. The primary exposure was household cooking fuel (clean vs. unclean per WHO guidelines). Outcomes were (1) stillbirth, defined as fetal loss at ≥7 months’ gestation, and (2) stillbirth rate per 1,000 total births. Survey-weighted bivariate screening (p < 0.05) identified candidate covariates for inclusion in multivariable, survey-weighted logistic regression models. Adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were reported. Given the cross-sectional design, estimates reflect associations, not causation.ResultsThe overall stillbirth rate was 15.85 per 1,000 births. Unclean cooking fuel use was associated with 44% higher odds of stillbirth (AOR: 1.44; 95% CI: 1.05–1.99; p = 0.0258). Other factors associated with higher odds were age ≥30 years (AOR: 2.17; 95% CI: 1.59–2.95; p < 0.001), moderate-to-poor health (AOR: 1.78; 95% CI: 1.39–2.28; p < 0.001), and alcohol consumption (AOR: 1.43; 95% CI: 1.06–1.93; p = 0.0195).DiscussionIn this nationally representative sample, unclean cooking fuel use was associated with increased odds of stillbirth. Expanding access to clean fuels and leveraging antenatal care services for culturally responsive clean-energy counseling may help reduce stillbirth risk. Prospective studies with exposure monitoring are needed to establish temporality.